A PLS-structural equation modelling of the role of financial inclusion, financial technology, financial stability, and bank competition on economic growth in ASEAN - Chua, Lou Marie Princess Dimalibot (Animo Repository, 2021)
This study aims to explain the interconnectedness of financial inclusion, financial technology, financial stability, bank competition, and economic growth by using PLS-Structural Equation Modelling (PLS-SEM) on panel data of the ASEAN region. The structure of the study is considered non-linear because of the conceptual models' four pathways leading to economic growth. Given that the researchers used data taken from databases; Secondary data from the World Development Indicator (WDI) and International Monetary Fund (IMF). The study applied PLS- Structural Equation Modelling (SEM) to measure latent variables out of a dataset of their observed variables and their relationships with each other in a structural model.